2012
DOI: 10.1073/pnas.1211976109
|View full text |Cite
|
Sign up to set email alerts
|

Heritable yeast prions have a highly organized three-dimensional architecture with interfiber structures

Abstract: Yeast prions constitute a "protein-only" mechanism of inheritance that is widely deployed by wild yeast to create diverse phenotypes. One of the best-characterized prions, [PSI + ], is governed by a conformational change in the prion domain of Sup35, a translation-termination factor. When this domain switches from its normal soluble form to an insoluble amyloid, the ensuing change in protein synthesis creates new traits. Two factors make these traits heritable: (i) the amyloid conformation is self-templating; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
51
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(55 citation statements)
references
References 61 publications
4
51
0
Order By: Relevance
“…4). The increased expression of Hsp31 at the diauxic shift and in stationary phase could possibly be due to the stress of decreased nutrients or accumulation of metabolites associated with these growth phases and is part of a global transcriptional response program (70). An increase in Hsp31 expression in response to ROS has been observed previously (71), and we confirmed that our tagged strain behaved in a similar manner by demonstrating an increase in expression upon exposure to H 2 O 2 (Fig.…”
Section: Discussionsupporting
confidence: 89%
“…4). The increased expression of Hsp31 at the diauxic shift and in stationary phase could possibly be due to the stress of decreased nutrients or accumulation of metabolites associated with these growth phases and is part of a global transcriptional response program (70). An increase in Hsp31 expression in response to ROS has been observed previously (71), and we confirmed that our tagged strain behaved in a similar manner by demonstrating an increase in expression upon exposure to H 2 O 2 (Fig.…”
Section: Discussionsupporting
confidence: 89%
“…Examples are the fibrils formed from sup35 or pml17 protein. Sup35-derived fibrils play a role in phenotypic inheritance in yeast cells (33) and were found to adopt ring-like assemblies underneath the plasma membrane or dot-like cytoplasmic inclusions with a regular mosaic structure (33). Pml17 fibrils are important for melanosome formation, and tomographic studies revealed intracellular sheet likeassemblies that consist of parallel fibrils of pml17 protein (34).…”
Section: Discussionmentioning
confidence: 99%
“…The HET-s prion, implicated in non-genetic inheritance of yeast, forms a ␤-solenoid with its ␤-strands arranged in a triangular shape (4). Electron microscopy additionally suggests that yeast prion fibers are capable of forming higher-order structures linked by organizational elements (5). Spider silk, which shares key characteristics with amyloid fibers (6,7), is composed of ␤-crystalline blocks connected by unstructured segments, an architecture that gives rise to the exceptional properties of silk (8 -10).…”
mentioning
confidence: 99%